EMBEDDING ESG ANALYTICS INTO MANAGEMENT ACCOUNTING SYSTEMS: IMPLICATIONS FOR STRATEGIC DECISION-MAKING - Dewi Nidia Soepriadi; Christina Sososutiksno; Rita Atarwaman (Adisam Publisher, 2026)
The integration of Environmental, Social, and Governance (ESG) analytics into Management Accounting Systems (MAS) is increasingly becoming a major concern in addressing the demands of sustainability, accountability, and long-term strategic decision-making. This study aims to systematically examine how ESG analytics are integrated into management accounting systems and their implications for organizations' strategic decision-making processes. The research method used is a literature review by examining scientific articles, institutional reports, and reputable academic publications relevant to the topics of ESG, management accounting, and strategic decision-making. The results of the study indicate that embedding ESG analytics into MAS can expand the role of management accounting from merely a cost control tool to a strategic instrument that supports sustainable value creation. This integration enables management to internalize ESG risks and opportunities into strategic planning, performance measurement, and investment evaluation. However, the study also identifies several challenges, such as limited ESG measurement standards, the complexity of non-financial data, and the readiness of human resources and technology. Conceptually, this study confirms that ESG analytics in MAS has the potential to improve the quality of strategic decisions by holistically integrating financial and non-financial dimensions. This research is expected to provide theoretical contributions to the development of sustainable management accounting literature and serve as a practical reference for organizations in designing management control systems aligned with ESG principles.